Can exercise promote additional benefits on body composition in patients with obesity after bariatric surgery? A systematic review and meta‐analysis of randomized controlled trials - Giorjines Boppre; Florêncio Diniz‐Sousa; Lucas Veras; José Oliveira; Hélder Fonseca (Wiley, 2022)
Abstract Background Bariatric surgery is the most effective treatment for patients with severe obesity, but success rates vary substantially. Exercise is recommended after bariatric surgery to reduce weight regain but the effectiveness remains undetermined on weight loss due to conflicting results. It is also unclear what should be the optimal exercise prescription for these patients. A systematic review and meta‐analysis of randomized controlled trials on the effects of exercise on body weight (BW), anthropometric measures, and body composition after bariatric surgery was performed. Methods PubMed/MEDLINE®, EBSCO®, Web of Science® and Scopus® databases were searched to identify studies evaluating exercise effectiveness. Results The analysis comprised 10 studies (n = 487 participants). Exercise favored BW (−2.51kg; p = 0.02), waist circumference (−4.14cm; p = 0.04) and body mass index (−0.84kg·m−2; p = 0.02) reduction but no improvements in body composition. Combined exercise interventions were the most effective in reducing BW (−5.50kg; p < 0.01) and body mass index (−1.86kg·m−2; p < 0.01). Interventions starting >6‐months after bariatric surgery were more successful in reducing BW (−5.02kg; p < 0.01) and body mass index (−1.62kg·m−2; p < 0.01). Conclusion Exercise, combined exercise regimens and interventions starting >6‐months after bariatric surgery were effective in promoting BW, waist circumference and body mass index reduction. Exercise following bariatric surgery does not seem to favor body composition improvements.